2005
DOI: 10.1111/j.1365-2427.2005.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of shredders on leaf litter biofilms: the effect of light intensity

Abstract: 1. The effect of light intensity on the decomposition of poplar (Populus nigra) leaves and growth of the shredders, Asellus aquaticus and Gammarus pulex, was studied in a laboratory experiment. The response was studied along a gradient of six light intensities of 0, 5, 23, 54, 97 and 156 lmol m )2 s )1 . It was hypothesised that an increase in light intensity would increase growth of shredders, because of an increase of algae (i.e. food quality) in the leaf-biofilm. 2. Light intensity affected both leaf-biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 46 publications
6
72
1
Order By: Relevance
“…As leaf fall provides the most important source of potential energy for headwater stream ecosystems, alteration of leaf fall biomass, nutrient content or timing may have important ecological impacts. Meanwhile, alterations such as canopy reduction (Smock and McGregor 1988;Hetrick et al 1998;Hutchens and Benfield 2000), increases in canopy shading (Franken et al 2005;Benfield 2006;Minshall and Rugenski 2006) or an alteration of the timing of leaf shading (Benfield 2006;Minshall and Rugenski 2006) disrupt autochthonous pathways that are temporally important sources of energy, even in streams with dense riparian forests (Fausch et al 2002;Kiffney et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As leaf fall provides the most important source of potential energy for headwater stream ecosystems, alteration of leaf fall biomass, nutrient content or timing may have important ecological impacts. Meanwhile, alterations such as canopy reduction (Smock and McGregor 1988;Hetrick et al 1998;Hutchens and Benfield 2000), increases in canopy shading (Franken et al 2005;Benfield 2006;Minshall and Rugenski 2006) or an alteration of the timing of leaf shading (Benfield 2006;Minshall and Rugenski 2006) disrupt autochthonous pathways that are temporally important sources of energy, even in streams with dense riparian forests (Fausch et al 2002;Kiffney et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although sunlight has been observed to directly enhance the rate of decomposition of plant leaf litter through photo degradation (Gallo et al 2009), other studies have observed decomposition as being mediated by associated macrobiota (Franken et al 2005), microbiota (Francoeur et al 2006) and adsorption of nutrients by sediment (Avnimelech & Gad 2003). In our study, litter exposed to sunlight seem to be characterized by a higher abundance of microalgae and epifauna compared to litter incubated in the shade.…”
Section: Litter Decompositionmentioning
confidence: 43%
“…Sunlight has been demonstrated to accelerate the rate of decomposition of leaf litter either solely, by photochemical oxidation action (Gallo et al 2009), or in combination with the accelerated extracellular enzymatic action of the associated microbial communities (Francoeur et al 2006). Light intensity also increases algae biomass, density and composition, creating a rich energy source for shredders, which enhances the rate of plant litter decomposition by their grazing activity (Franken et al 2005).…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Alteration in the biological processes of streams has been suggested to be directly linked to the extent and cover of the adjacent riparian zone (Franken et al 2005). Terrestrial invertebrate and detrital inputs are recognised as a direct energy source for many high order consumers in aquatic systems, and their dependence on this is well documented (Power & Dietrich 2002;England & Rosemond 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of riparian vegetation associated with urbanisation has been shown to have detrimental effects on both stream morphology and fauna. Reductions in riparian zones and consequently terrestrial inputs including large woody debris (LWD) have been shown to reduce habitat and food availability, affect stream temperature and disrupt sediment, nutrient and toxin concentrations because of increased levels of surface run-off (Edwards & Huryn 1996;Cummins et al 1989;Franken et al 2005;Meyer et al 2005).…”
Section: Introductionmentioning
confidence: 99%